STUDI KOMPARASI PEMASARAN KARET SISTEM LELANG DAN KONVENSIONAL DAN KEBERDAYAAN EKONOMI PETANI KARET DI KECAMATAN KUANTAN TENGAH KABUPATEN KUANTAN SINGINGI - Yogi Tama Pangestu; Rosnita Rosnita; Roza Yulida (Program Studi Pendidikan Ekonomi Universitas Riau, 2018)
The aims of this research were to study: 1) to identify the rubber marketing ofauction system and conventional in Kuantan Tengah sub-district, 2) to identify theprofile of rubber farmers of auction and conventional system in Kuantan Tengahsub-district; 3) to analyze the rubber marketing of auction system and conventionalin Kuantan Tengah sub- . The sample of farmers in this study amounted to 88people consisting of 29 samples of auction farmers and 59 samples of conventionalfarmers. The results of the study illustrated before the existence of auction marketprice is controlled by large traders (toke). Conventional farmers were dominated byfarmers who had land area under 2 hectares. Profile of rubber farmers using auctionmarketing system that was 100 percent of men productive age of 65.52 percent, theaverage of elementary education, the number of family dependents 0 to 3 withpercentage of 51.72 percent, land ownership of farmers over 2 hectares with apercentage of 58 , 62 percent and 100 percent own ownership status and longexperience of farmers 6-10 years farming with a percentage of 44.83 percent, of 59samples of conventional farmers were men, the age of productive farmers amountedto 43 farmers with a percentage of 72.88 percent, 18 farmers who worked as farmlaborers on the land of others, there was no difference between the average profit ofthe trader (toke), there was a difference between the average marketing costs offarmers, there was a difference between the average marketing margin, there was adifference between the average efficiency marketing.